Prevalence of Orofacial Clefts and Associated Factors in Infants - S Khosroshahian (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Orofacial clefts are the most common congenital facial defect. Genetic and environmental factors play a role in their development. The prevalence of orofacial clefts in Qom province has not been studied so far. The aim of this study was to evaluate the prevalence of orofacial clefts and associated factors in infants born in Qom province during 2010-2018. METHODS: In this cross-sectional study, during nine years, the medical files of all infants with orofacial clefts and the files of their mothers in all hospitals of Qom province were examined. The files of 476 healthy infants were also evaluated to investigate the associated factors. Healthy infants were selected one number before and one after the case number of sick infants. Infant-related variables (weight, blood type, and other illnesses) and parent-related factors (age, smoking, alcohol, and medications, illness, consanguineous marriage, and number of children) were extracted through reviewing the files or telephone interview. FINDINGS: Of the 171,270 infants, 238 were found with orofacial clefts (1.39 per 1,000 births). Isolated cleft palate with 39.5% was the most common type of anomaly. Among the studied factors, the percentage of smoking in fathers in the case group (34.5%) was higher than the control group (24.2%) (p=0.004). Moreover, the history of maternal high blood pressure in the case group (7.6%) was higher than the control group (3.4%) (p=0.013). The incidence of diabetes in mothers of the case group (18.9%) was higher than the control group (8.2%) (p=0.001). CONCLUSION: The results of the study showed that the prevalence of orofacial cleft is 1.39 per 1000 births and smoking, diabetes and high blood pressure are the associated risk factors.